Introduction of Kazakhstan species of Irises (Experimental biology, 2020)
According to various sources 19 (22) species are found in the flora of Kazakhstan except 3 rare species (Iris alberti Regel, I. ludwigii Maxim, I. tigridia Bunge) and endemics I. ludwigii, I. alberti. Eight species are used in folk medicine. Most of the wild irises grow in southeast Kazakhstan in various environmental conditions where they are found from the foothills and slopes of Dzungarian Alatau and the North Tien Shan mountains up to the desert territory of the Balkhash-Alakol depression.We studied introducted species of the genus Iris L. attracted in 2015–2019 by living plants from natural habitats (foothills of the Zailiysky Alatau, South. Balkhash) as well as, seeds by delectus exchange. In order to restore the collection of species belong to Iris L. on the site of medicinal plants have studded the features of their seasonal development, fruiting and seed propagation under conditions of small plot cultivation in the territory of MBG.In the studies have been used generally accepted introduction methods with their slight modifications as applied to local conditions.As a result of studies, it was found that the tested species of irises tolerate translocation well. All 4 species transferred to the culture by rhizomes undergo a normal cycle of phenological development, flowering, 2 species regularly give matured seeds.Seed propagation of wild irises gives extremely low results which are further exacerbated by the seedling germination cycle extended over the years that again confirms the above literature data on their low seed reproduction potential. At the same time, some of the pre-sowing treatment options that we tested give reason to believe that it is promising to develop more effective methods for seed propagation of irises.Key words: irises, introduction, Kazakhstan